2001
DOI: 10.1021/jf010539w
|View full text |Cite
|
Sign up to set email alerts
|

Formation of Furfurylthiol Exhibiting a Strong Coffee Aroma during Oak Barrel Fermentation from Furfural Released by Toasted Staves

Abstract: Furfurylthiol (FFT) is formed in white wines during alcoholic fermentation in the barrel from the furfural released by toasted staves. The quantity of furfural released into the must has a decisive effect on the quantity of FFT in the finished wine. Wines fermented in new barrels thus contain larger quantities of FFT than those fermented in used barrels. Fermentation conditions favorable to an excess production of H(2)S (hydrogen sulfide) by the yeast promote the formation of this volatile thiol. The presence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
76
0
5

Year Published

2002
2002
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 84 publications
(81 citation statements)
references
References 9 publications
0
76
0
5
Order By: Relevance
“…The individual compounds responsible for flavour or off-flavour of wine are often present at extremely low concentration (e.g. less than 1 µg L -1 [1,2,3,4,5]). Therefore the analytical methods for detecting these compounds in wine are required to be at least as sensitive as the human nose.…”
Section: Introductionmentioning
confidence: 99%
“…The individual compounds responsible for flavour or off-flavour of wine are often present at extremely low concentration (e.g. less than 1 µg L -1 [1,2,3,4,5]). Therefore the analytical methods for detecting these compounds in wine are required to be at least as sensitive as the human nose.…”
Section: Introductionmentioning
confidence: 99%
“…We think that the generation of 2FM in our media was not related to β-(C-S) lyase, because all of the media were adjusted to pH 5.2 before fermentation, and the average pH value was 4.6 at the end of fermentation. Blanchard et al 14) have reported that the quantity of 2FM produced was proportional to the amount of cysteine added to the medium. Our results for the generation of 2FM in the soy sauce media are in accord with the data of Blanchard et al The concentration of 2FM in our media was greatest at a high concentration of cysteine.…”
Section: Key Precursor Compound For 2fm Generationmentioning
confidence: 99%
“…In addition, Muench et al 27) have reported that the formation concentration of 2FM from glucose and cysteine showed a maximum at pH 5.0. Huynh-Ba et al 28) have reported that baker's yeast catalyzed the transformation of a cysteine-furfural conjugate into 2FM at pH 8.0, while Blanchard et al 14) have reported that 2FM was formed by yeast from furfural and cysteine in white wine at pH 3.5. A pH value of 4.7 for soy sauce is therefore advantageous for generating 2FM by yeast during alcoholic fermentation, and the results of our experiments with soy sauce samples confirmed that 2FM can be generated by yeast.…”
Section: Formation Of 2fm By Yeastmentioning
confidence: 99%
See 1 more Smart Citation
“…Among several industrial chemicals and biochemicals manufactured, 2-furaldehyde (furfural, F) is very important owing to its wide applications [1 -5] and its unique availability from agricultural wastes and forest residues [6]. Furfural is an irritant of the skin, eyes, mucous membranes and respiratory tract and may also cause unconsciousness.…”
Section: Introductionmentioning
confidence: 99%